Enhanced dielectric properties and conductivity of triturated copper and cobalt nanoparticles-doped PVDF-HFP film and their possible use in electronic industry. (16th April 2017) - Gayen, A. L.; Paul, B. K.; Roy, D.; Kar, S.; Bandyopadhyay, P.; Basu, R.; Das, S.; Bhar, D. S.; Manchanda, R. K.; Khurana, A. K.; Nayak, D.; Nandy, P.
Abstract : We have synthesised a novel nanocomposite film by incorporating copper and cobalt nanoparticles, prepared by the method of trituration, in the poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) films by simple solution-casting technique. Fourier transform infrared spectroscopy (FTIR) study of these nanocomposite films detected presence of α - and β -phases. Scanning electron micrographs showed spherulitic crystal structure of PVDF-HFP in the nanocomposite film and study of dielectric properties over broadband frequency of these doped nanocomposite film showed that these films have higher dielectric permittivity and significantly lower dissipation factor (tan δ ) at room temperature compared to the pure PVDF-HFP. The incorporation of metallic nanoparticles in the polymer matrix activates the transition of phase between α and β and provides the nanocomposites higher mobile charge carriers which participate in the interfacial polarisation. The room temperature dielectric constant of the pure PVDF-HFP at 20 Hz frequency increases with increase in concentration of the metal nanoparticles and reaches a maximum almost four times the value of the pure one. At higher concentrations, the effect reduces, perhaps due to agglomeration of the nanoparticles. The metal nanoparticles, obtained by the method of trituration, are inexpensive, easy to fabricate and environment friendly. Thus, their incorporation in polymer matrix to get enhanced electrical properties will have a significant contribution to the present day research.